PENERAPAN MODEL ANTREAN MULTI CHANNEL SINGLE PHASE PADA SISTEM PELAYANAN RESTORAN CEPAT SAJI - NI WAYAN EKANTARI, NI WAYAN; TASTRAWATI, NI KETUT TARI; SARI, KARTIKA (E-Jurnal Matematika, 2021)
A queue will occur if the average number of arrivals exceeds the capacity of service facilities. Fast food restaurants are one of the places that usually have long queues at lunchtime and dinner time. KFC in Bali, located in the village of Sanur, is a fast food restaurant that is experiencing long queues. This is because this restaurant is located in a tourism area and the only KFC outlet on the Ngurah Rai Sanur bypass line and does not yet have a drive-thru service. The current condition at KFC Sanur is that there is more than one service facility, disciplined first come first service (FCFS) queues according to the multi channel single phase queuing model. After being analyzed with data taken before the pandemic period on November 18, 2019 to December 1, 2019 for 14 days during weekdays and weekends, it was found that the performance of the KFC Sanur queue system would have a smaller utility level if there were 3 active server . The total cost per customer if there are 2 active server is IDR 78,692.38 and if there are 3 server is IDR 75,788.45. Based on the results of this analysis, it can be concluded that it will be more optimal if there are 3 active server .